ETIKA KRISTEN DAN KAITANNYA DENGAN PEMBENTUKAN KARAKTER KRISTIANI - Purba, Vivi May Christi; Sibuea, Hesty Martini; Imeldawati, Tiur; Nainggolan, Regina BM (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This research aims to explain Christian ethics and its relationship to the formation of Christian character. What should be done to form Christian character in the current generation of young Christians as successors to the future of the church and the future of the nation? What things can be done as an effort to form Christian character as taught in the Bible? This research was carried out using qualitative methods and is useful for Christian educators who are involved in Christian ministry. Apart from educators, this research is also useful for Christian pupils and students who continue to study and strive to have Christian character as taught by Jesus.Key words: ethics, generation, Christian character